The Role of Exchange Rate Policy in Trade Balance Adjustment: Investigating the Industry-Level Bilateral Trade Between Egypt and Italy - ElMasry, Nervan (AUC Knowledge Fountain, 2021)
The study in hand attempted an empirical test for the impact of exchange rate policy on Egypt’s persistent trade balance (TB). To address the issue of “aggregation bias,” the study employed quarterly disaggregated trade data over the period 2007Q1-2019Q4 to capture the recent foreign exchange rate evolution in Egypt. The study applied a bounds test based on an Autoregressive Distributed Lags (ARDL) in its linear and non-linear form to empirically examine the long-run co-integrating relation between the variables and an error correction model (ECM) to estimate the short run dynamics of the adjustment process. The study compared the symmetrical against the asymmetrical responses of the selected 10 traded commodities based on the Harmonized System (HS) Chapters aiming to quest the occurrence of the J-shaped pattern. Evidently, the empirical test asserted the existence of a long-run relationship in 40% of the industries estimated by linear ARDL. Further, the non-linear ARDL process for 2 of these 4 industries validated the significant long-run relationship, and an asymmetrical relationship was detected for 2 Chapters. Moreover, the findings of the study did not detect a statistically significant short run relationship between real exchange rate and industry level TBs except for 2 industries within the non-linear ARDL process. For the “J-curve effect” quest, the study did not support the observance of the J-shaped pattern in any of the responses of the 10 selected industries. The findings suggest that the RER movements did not yield an immediate trade deficit correction in the case of Egypt bilateral trade with Italy, yet they exhibited long run corrective properties in certain industries.